2006
DOI: 10.1097/00006416-200611000-00007
|View full text |Cite
|
Sign up to set email alerts
|

NIOSH Research Efforts to Prevent Musculoskeletal Disorders in the Healthcare Industry

Abstract: Healthcare workers, including orthopaedic nurses, face a number of risk factors in the workplace for musculoskeletal disorders such as back and shoulder injuries. These disorders are associated with excessive back and shoulder loading due to manual patient handling, applying excessive forces during pushing and/or pulling of objects, required use of awkward postures during patient care, and working long hours and shiftwork. No healthcare workers are immune from injury because workers in all clinical areas are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(112 citation statements)
references
References 11 publications
4
103
0
5
Order By: Relevance
“…The tasks that nurses and nursing assistants are expected to perform on a daily basis involves large amounts of weight, awkward postures, confined working environments, excessive manual forces, extended task duration, and high frequency/repetitions. Health care worker experiences a number of risk factors for musculoskeletal disorders in the workplace, such as back and shoulder injuries [12]. The frequency and severity of the contact to these risk factors differ, depending on the type of healthcare setting.…”
Section: Introductionmentioning
confidence: 99%
“…The tasks that nurses and nursing assistants are expected to perform on a daily basis involves large amounts of weight, awkward postures, confined working environments, excessive manual forces, extended task duration, and high frequency/repetitions. Health care worker experiences a number of risk factors for musculoskeletal disorders in the workplace, such as back and shoulder injuries [12]. The frequency and severity of the contact to these risk factors differ, depending on the type of healthcare setting.…”
Section: Introductionmentioning
confidence: 99%
“…Unsafe patient handling is a major risk factor for musculoskeletal injuries among nurses (Waters et al, 2006). Each year, more than 10,000 nurses in the United States experience work-related musculoskeletal disorders resulting in lost work days and nurses rank among the top five occupations for musculoskeletal disorders (Bureau of Labor Statistics, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Investigating the impact of each physical demand item showed that awkward body posture, repetitive motions and pressure with hands or wrists are associated with prevalence of LBDs independently. Many studies have shown that perceived physical demands such as polling/pushing heavy objects, moving/lifting/lowering heavy load, performing repetitive motions with hands/wrist and bending or twisting the body were significantly associated with MSDs [28,29,30,31]. The results of the present study are in accordance with the findings of Choobineh, Rajaeefard and Neghab's study which found that high levels of perceived physical demands (scores 10-12 of JCQ) were significantly associated with prevalence of LBDs compared to low-medium levels (scores 0-9 of JCQ).…”
Section: Discussionmentioning
confidence: 99%